Selective Semihydrogenation of Phenylacetylene to Styrene Catalyzed by Alloyed Palladium/Gold Catalysts Anchored on Cerium Oxide. Issue 5 (23rd March 2018) - Zhang, Sai; Xia, Zhaoming; Chen, Xiao; Gao, Wei; Qu, Yongquan
Abstract: Chemoselective semihydrogenation of alkynes to alkenes is a significant organic transformation and long challenge for heterogeneous catalysts. Herein, the PdAu alloyed nanoparticles were successfully deposited on the surface of cerium(IV) oxide nanorods ( NR ‐CeO2 ) through an electroless chemical deposition process. Alloyed catalysts had an enhanced catalytic activity for hydrogenation of phenylacetylene and improved selectivity towards styrene, compared with the Pd/ NR ‐CeO2 and Au/ NR ‐CeO2 catalysts. The enhanced catalytic activity can be attributed to the alloying effects. Furthermore, the weak adsorption of styrene obtained from the modulated surface characteristics also benefits the improved chemoselectivity. Abstract : Alloyed PdAu nanoparticles with a low palladium content were successfully deposited on the surface of CeO2 nanorods ( NR ‐CeO2 ) through an electroless chemical deposition process. The alloying effects and modulated surface characteristics benefit the selective semihydrogenation of phenylacetylene to styrene.